Suicidality and Non-Suicidal Self-Injury: A Narrative Review of Measurement, Risk, and Disparities among Minoritized and System-Involved Youth in the USA - Melissa L. Villodas (MDPI AG, 2024)
Suicidality and non-suicidal self-injury (NSSI) among youth in the United States continue to be a growing and serious public health concern. With alarming rates of suicide trending in the wrong direction, researchers are committed to bending the curve of suicide and reducing rates by 2025. Understanding the antecedents and conditions, existing measures, and disparate prevalence rates across minoritized groups is imperative for developing effective strategies for meeting this goal. This study presents a narrative review of the operationalization, measurement, risk factors (e.g., firearms and social media), and disparities across race, ethnicity, age, gender identity, ability, sexual orientation, immigration statuses, and system involvement (e.g., foster care and juvenile justice) of suicidality and non-suicidal self-harm across youth in the United States. Implications for research, practice, and policy approaches that incorporate positive youth development, cultural, and youth participation in interventions are discussed.